Plastic pollution of the world’s seas and oceans as a contemporary challenge in ocean governance - Marcus Haward (Nature Portfolio, 2018)
The pervasive nature of marine plastic pollution was highlighted at the recent United Nations Environment Assembly. This meeting saw strong commitments for action, but at the same time reinforced the challenges for contemporary ocean governance in addressing marine plastic pollution.